The Impact of Currency Union on Trade Imbalances The Case of Eurozone - Bednář, Ondřej (2014)
The purpose of the thesis is to investigate the impact of accession of a common currency on trade imbalances. Why Common currency? It is highly debated topic how the common currency in European Union influences its economy. Moreover, many countries of the European Union are about to join or are considering entering Eurozone. Why trade imbalances? Trade imbalances have gone through rapid development during last two decades. Therefore, they attracted attention of many economists. What method? The papers of economists who research trade imbalances was used as main inspiration and motivation to write the thesis. The paper is called Wearing corset, losing shape (2010) and is written by Helge Berger and Volker Nitsch. In the following paragraphs, there are more comprehensive answers to the three above stated questions.